1993
DOI: 10.1002/rsa.3240040204
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of random plane‐oriented recursive trees and their branches

Abstract: This paper is an investigation of the structural properties of random plane-oriented recursive trees and their branches. We begin by an enumeration of these trees and some general properties related to the outdegrees of nodes. Using generalized Polya urn models we study the exact and limiting distributions of the size and the number of leaves in the branches of the tree. The exact distribution for the leaves in the branches is given by formulas involving second-order Eulerian numbers. A martingale central limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 14 publications
6
78
0
Order By: Relevance
“…The most studied case is that of a uniform choice, but probabilities essentially proportional to degrees have also been considered. Such objects (where for the first vertex degree plus one is used) are known as random plane-oriented recursive trees, see [27,21], for example. Pittel [24] showed that the height (maximum distance of a vertex from the root) of such an object is (c + o(1)) log n with probability 1 − o (1), where c = (2γ) −1 for γ the solution of γe 1+γ = 1.…”
Section: The Case M =mentioning
confidence: 99%
“…The most studied case is that of a uniform choice, but probabilities essentially proportional to degrees have also been considered. Such objects (where for the first vertex degree plus one is used) are known as random plane-oriented recursive trees, see [27,21], for example. Pittel [24] showed that the height (maximum distance of a vertex from the root) of such an object is (c + o(1)) log n with probability 1 − o (1), where c = (2γ) −1 for γ the solution of γe 1+γ = 1.…”
Section: The Case M =mentioning
confidence: 99%
“…Hence, the combined contribution of (4) and (5) is 3 − 24 (i + j + 4) 4 , which completes the proof.…”
Section: Letter To the Editormentioning
confidence: 55%
“…In 2005 Janson [3], extending the earlier work of Mahmoud et al [4], established the joint asymptotic normality of the outdegrees of a random plane recursive tree (we refer to [3] for references, discussion, and statements, and to [2] for a much wider context). In particular, he gave the following formula for the entries of the limiting covariance matrix [ …”
mentioning
confidence: 91%
“…where p n (d) denotes the probability that a random node in random PORT of size n has degree d (see [9] or [8]). Now, we introduce a substitution process that creates random graphs that have a global tree structure that is governed by plane oriented recursive trees.…”
Section: Thickened Treesmentioning
confidence: 99%